INCLUSIVITY OF INDIGENOUS WOMEN OF KASHMIR IN DISASTER MANAGEMENT - Bilquees Dar; Keerti Sharma; Muzzafar Kawa (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
In recent years, the increasing awareness of disasters has lead to the change in the perception of threat to disasters manifoldly in Jammu & Kashmir particularly after 2014 floods and Covid 19 Pandemic. Disasters and its effect on public consciousness has become one of the most noticeable trends on a global level. Jammu and Kashmir has seen all types of disasters in past ranging from Earthquakes to floods, fires, Droughts, Pandemic etc. Despite of global community's unfulfilled promise of a society in which every woman enjoys complete gender equality, as well as the eradication of all legal, social, and economic obstacles to women empowerment, persists in Kashmir .Women comprise the largest proportion of the impoverished are the most vulnerable and disadvantaged group but in this indigenous community of Dal Dwellers in Srinagar, it has been found that women were more involved in Disaster Response and relief ranging from providing food to providing shelters to the affected people. This community depends more on natural resources, but has less access to them. In fact, they often face a significant burden for procuring food, water, and fuel. These areas are mostly threatened by Floods. In Kashmir women is consider as agent beyond these disasters. Hence an attempt has been made to emphasis the aura Dal Lake and women inclusivity in Disaster Management..